Is There a Role for Cartilage Imaging in Athletes? - Yamamoto, Asako; Levine, Benjamin D.; Padron, Mario; Chung, Christine B. (Seminars in Musculoskeletal Radiology, 2020)
This article reviews implications for cartilage imaging in athletes in the setting of (1) acute chondral injury diagnosis, (2) evaluation and follow-up of conservative and surgical therapy, and (3) evaluation of cartilage as a surrogate for meniscal function and joint stability. Focal knee cartilage defects are common in athletic populations. Athletes with articular cartilage injury may initially be able to return to sport with conservative therapy; however, a reduction of athletic ability and progression to osteoarthritis is expected in athletes with untreated severe chondral injury. For diagnostic and pre- and postsurgical evaluation purposes, morphological magnetic resonance (MR) assessment of the articular cartilage with high-resolution protocols is crucial. Although not widely implemented for clinical use, compositional MR techniques have great potential for monitoring the development and progression of biochemical and microstructural changes in cartilage extracellular matrix before gross morphological changes occur.
Keywords: articular cartilage; knee; athlete; magnetic resonance imaging; cartilage repair